HUBUNGAN PROKRASTINASI AKADEMIK DAN ACADEMIC BURNOUT PADA MAHASISWA - Gabriel Fransisca Gunawan; Lena Nessyana Pandjaitan (Perpustakaan Universitas Surabaya, 2024)
Abstract—Pharmacy students have assignment demands such as journal writing, reports, presentations, and practical work. Facing these numerous assignments can lead to academic burnout. Academic burnout is a state where an individual experiences emotional exhaustion caused by factors such as high task demands, feelings of incompetence in fulfilling student obligations, and a decline in performance. The main cause of this is the tendency of students to delay or engage in academic procrastination when facing task burdens. This study aims to examine the relationship between academic procrastination and academic burnout among students. The sample for this research consisted of 151 students from the Faculty of Pharmacy at Surabaya University. The research employed a quantitative survey method, collecting data through the modified Maslach Burnout Inventory scale by Schaufeli and the Academic Procrastination Scale (APS) proposed by McCloskey. The sampling technique used in this study was accidental sampling. The results of this research indicate a significant relationship between academic procrastination and academic burnout among students (sig 0.000 < 0.05). With a positive correlation, higher levels of academic procrastination are associated with higher levels of academic burnout. Furthermore, there was also a significant association found between self-efficacy and academic burnout, with a value of 0.048 < 0.05. Keywords: academic procrastination, academic burnout, pharmacy faculty students, self-efficacy Abstrak—Mahasiswa Farmasi memiliki tuntutan penugasan berupa pembuatan jurnal, laporan, presentasi, serta praktikum. Dalam menghadapi banyaknya penugasan tersebut dapat menimbulkan academic burnout. Academic burnout adalah keadaan seseorang yang mengalami rasa lelah secara emosional diakibatkan oleh faktor tuntutan tugas yang banyak, perasaan tidak kompeten dalam menjalankan kewajiban sebagai mahasiswa, hingga pada merosotnya prestasi. Penyebabnya adalahnya dalam menghadapi beban tugas tersebut mahasiswa kerap melakukan penundaan atau prokrastinasi akademik. Penelitian ini bertujuan untuk menguji hubungan antara prokrastinasi akademik dan academic burnout pada Mahasiswa. Sampel pada penelitian ini adalah 151 Mahasiswa Fakultas Farmasi Universitas Surabaya. Penelitian ini merupakan penelitian dengan metode kuantitatif survei dengan pengumpulan data melalui skala Maslach Burnout Inventory yang telah dimodifikasi oleh Schaufeli dan skala Academic Procrastination Scale (APS) yang dikemukakan McCloskey. Teknik pengambilan sampel pada penelitian ini menggunakan insidental sampling. Hasil pada penelitian ini menunjukkan bahwa terdapat hubungan yang signifikan antara prokrastinasi akademik dan academic burnout pada Mahasiswa (sig 0,000 < 0,05). Dengan memperoleh korelasi positif maka semakin tinggi prokrastinasi akademik maka akan semakin tinggi pula academic burnout, selain itu juga ditemukan asosiasi antara keyakinan akan kemampuan diri dan academic burnout sebesar 0,048 < 0,05. Kata kunci: prokrastinasi akademik, academic burnout, mahasiswa fakultas farmasi, keyakinan akan kemampuan diri